Pengaruh Segmentasi Pengaruh Segmentasi Pasar Terhadap Pasar Terhadap Peningkatan Penjualan Peningkatan Penjualan Meeting Package Meeting Package Morrissey Hotel Jakarta - Arianti, Qotrunnada Maghfirah; Astuti, Anindita Budi; Pinandoyo, Dimas Bayu (LPPM Politeknik Pajajaran ICB Bandung, 2024)
ABSTRACT The increasingly competitive hospitality industry requires hotels to implement appropriate marketing strategies to boost sales, one of which is market segmentation. Inadequate application of effective segmentation may hinder the sales growth of hotel products, including meeting packages. Based on this issue, this study aims to analyze the effect of market segmentation on the sales improvement of meeting packages at Morrissey Hotel Jakarta. This research employs a quantitative method with a descriptive approach. Data were collected through questionnaires distributed to 100 respondents who are users of the meeting package services. The data analysis technique used in this study is descriptive statistics and Spearman rank correlation test. The results show that market segmentation based on demographic, psychographic, behavioral, and geographic factors has a positive and significant effect on meeting package sales. Hypothesis testing confirms a significant relationship between market segmentation and meeting package sales improvement. By applying the right segmentation strategy, Morrissey Hotel Jakarta can effectively increase sales by targeting more specific market segments. Keywords: Market Segmentation, Sales, Meeting Package, Morrissey Hotel Jakarta.